Divalent cations permeation in a Ca2+ non-conducting skeletal muscle dihydropyridine receptor mouse model. (November 2020) - Idoux, Romane; Fuster, Clarisse; Jacquemond, Vincent; Dayal, Anamika; Grabner, Manfred; Charnet, Pierre; Allard, Bruno
Graphical abstract: Highlights: Skeletal muscle dihydropyridine receptor functions as a voltage-gated Ca 2+ channel. N617D mutation in the DHPRα1S subunit abolishes Ca 2+ permeation through the channel. Ba 2+ and Mn 2+ ions are found to permeate the N617D mutant channel. External Ca 2+ strongly blocks Ba 2+ currents through the mutant channel. N617D mutation located outside the selectivity filter influences channel permeation. Abstract: In response to excitation of skeletal muscle fibers, trains of action potentials induce changes in the configuration of the dihydropyridine receptor (DHPR) anchored in the tubular membrane which opens the Ca 2+ release channel in the sarcoplasmic reticulum membrane. The DHPR also functions as a voltage-gated Ca 2+ channel that conducts L-type Ca 2+ currents routinely recorded in mammalian muscle fibers, which role was debated for more than four decades. Recently, to allow a closer look into the role of DHPR Ca 2+ influx in mammalian muscle, a knock-in ( ki ) mouse model ( nc DHPR) carrying mutation N617D (adjacent to domain II selectivity filter E) in the DHPRα1S subunit abolishing Ca 2+ permeation through the channel was generated [Dayal et al., 2017]. In the present study, the Mn 2+ quenching technique was initially intended to be used on voltage-clamped muscle fibers from this mouse to determine whether Ca 2+ influx through a pathway distinct from DHPR may occur to compensate for the absence of DHPR Ca 2+ influx. Surprisingly, while N617D DHPR muscle fibers of the ki mouse do not conduct Ca 2+, Mn 2+ entry and subsequent quenching did occur because Mn 2+ was able to permeate and produce L-type currents through N617D DHPR. N617D DHPR was also found to conduct Ba 2+ and Ba 2+ currents were strongly blocked by external Ca 2+ . Ba 2+ permeation was smaller, current kinetics slower and Ca 2+ block more potent than in wild-type DHPR. These results indicate that residue N617 when replaced by the negatively charged residue D is suitably located at entrance of the pore to trap external Ca 2+ impeding in this way permeation. Because Ba 2+ binds with lower affinity to D, Ba 2+ currents occur, but with reduced amplitudes as compared to Ba 2+ currents through wild-type channels. We conclude that mutations located outside the selectivity filter influence channel permeation and possibly channel gating in a fully differentiated skeletal muscle environment.